Kalimatun Sawa’ as The Basis of Religious Tolerance (Interpretation of Nurcholish Madjid’s Thoughts Based on Paul Ricoeur’s Hermeneutics) - Haryati, Tri Astutik; Zuhri, Amat; Marom, Naelil (IAIN Pekalongan, 2020)
This paper aims to understand deeply the thoughts of Nurcholish Madjid about kalimatun sawa’ as the basis of religious tolerance. The approach used is Paul Ricoeur’s Hermeneutics. The main issues that will be examined include interpretation theory in Paul Ricoeur’s Hermeneutics, Nurcholish Madjid’s thoughts about kalimatun sawa’, as well as the application of interpretation theory in understanding kalimatun sawa’. Through this understanding, it is expected to find the meaning of kalimatun sawa’ as well as its contribution to religious tolerance in Indonesia.